The synthesis of the CeO(2)-PrO(2)-Ln(2)O(3) pigments - Šulcová, Petra; Trojan, Miroslav (Univerzita Pardubice, 2000)
The synthesis of new inorganic pigments based on CeO2-PrO2-Ln2O3 has been investigated. The main attention is directed to the preparation of these pigments which can be used for colouring ceramic glazes. The synthesis of these pigments is based on high-temperature calcination of starting oxides. The optimum conditions for the syntheses of pigments have been istimated and the pigments prepared have been evaluated from the standpoint of their structure, colour hue and ability to dye ceramic glazes.
Keywords: syntézy; anorganické pigmenty; lanthanoidy